Do Political Instability and Size of GovernmentimpactEconomic Growth in Pakistan: New Insights from Tada and Yamamoto Causality - Iqbal, Sehrish; Yasmin, Fouzia; Nasir, Nazia; Safdar, Noreen (The journal of contemporary issues in business and government, 2021)
Present research explores the role ofthe size government in economicdevelopment. The research endeavors to investigate the impact of political instability, size of theGovernment on economic growth in Pakistan. The data on political instability iscollected from Integrated Network for Societal Conflict Research and the indicator forthese variables is Polity II. Data for the size of the Government is taken from theEconomic Freedom of the World Annual Report (2019). The annual time series data covering the period of 1976to2018forempiricalanalysis.ARDL and the granger non-causality Tota- Yamamo to estimation techniques have been used for empirical estimation. It was concluded that political instability has inverse impact on economic growth. The size of the government as measured by index and reduction in political instability have positive impact on economic growth. It was suggested to enhance the role of the government to promote economic growth that further led to economic growth.